Forecasting sunspot numbers with Feedforward Neural Networks (FNN) using 'sunspot neural forecaster' system - Reza Ezuan, Samin; Muhammad Salihin, Saealal; Azme, Khamis; Syahirbanun, Isa; Ruhaila, Md. Kasmani (IEEE, 2011)
This paper presents the investigations of forecasting performance of different type of Feedforward Neural Networks (FNN) in forecasting the sunspot numbers. Feedforward Neural Network will be used in this investigation by using different learning algorithms, sunspot data models and FNN transfer functions. Simulations are done using Matlab 7 where customized Graphic User Interface (GUI) called `Sunspot Neural Forecaster' have been developed for analysis. A complete analysis for different learning algorithms, sunspot data models and FNN transfer functions are examined in terms of Mean Square Error (MSE) and correlation analysis. Finally, the best optimized FNN parameters will be used to forecast the sunspot numbers.